Testing Dark Matter with the Anomalous Magnetic Moment in a Dark Matter Quantum Electrodynamics Model - Gamboa-Rios, J; Mendez-Ferrada, F (World Scientific Publishing Co. Pte Ltd, 2017)
We consider a model of dark quantum electrodynamics (QEDs) which is coupled to a visible photon through a kinetic mixing term. We compute the gχ - 2 for the dark fermion, where gχ is its gyromagnetic factor. We show that the gχ - 2 of the dark fermion is related to the gχ′ - 2 of (visible) QEDs through a constant which depends on the kinetic mixing factor. We determine gχ - 2 as a function of the mass ratio κ = mB/mχ, where mB and mχ denote the masses of the dark photon and the dark fermion, respectively, and we show how gχ - 2 becomes very different for light and heavy fermions around mB ≤ 10-4 eV. © 2017 World Scientific Publishing Company.